2014
DOI: 10.1186/s13018-014-0050-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency bipolar hemostatic sealer reduces blood loss, transfusion requirements, and cost for patients undergoing multilevel spinal fusion surgery: a case control study

Abstract: BackgroundA relatively new method of electrocautery, the radiofrequency bipolar hemostatic sealer (RBHS), uses saline-cooled delivery of energy, which seals blood vessels rather than burning them. We assessed the benefits of RBHS as a blood conservation strategy in adult patients undergoing multilevel spinal fusion surgery.MethodsIn a retrospective cohort study, we compared blood utilization in 36 patients undergoing multilevel spinal fusion surgery with RBHS (Aquamantys®, Medtronic, Minneapolis, MN, USA) to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…It has been proven also to reduce blood loss and improve visualization during spinal surgery (8,14,19). A recent report of its application in brain tumour resection has demonstrated similar benefits in terms of reducing blood loss.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…It has been proven also to reduce blood loss and improve visualization during spinal surgery (8,14,19). A recent report of its application in brain tumour resection has demonstrated similar benefits in terms of reducing blood loss.…”
Section: Discussionmentioning
confidence: 79%
“…The combination of RF energy and saline provides haemostatic sealing of tissues, without charring or carbonisation. It has been widely adopted in a number of other surgical specialties, including orthopaedic, hepatobiliary and neurosurgery (8)(9)(10). Reports in the literature of the use of the Aquamantys ® system in a thoracic surgical setting are limited and deal with older, lower-energy models of the device that proved inefficient at sealing lung tissue (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…For spine surgeons, the Aquamantys System (Medtronic, Minneapolis, MN, USA) has grown in popularity after studies have shown its efficacy in the reduction in surgical blood loss and transfusion rates [38][39][40]. This device uses bipolar RF energy combined with saline irrigation to deliver controlled thermal energy to the soft tissues.…”
Section: Electrocauterymentioning
confidence: 98%
“…Newer methods of electrocautery that more effectively achieve hemostasis, along with topical hemostatic agents and sealants, are also effective in reducing blood loss . In procedures expected to be associated with significant blood loss, we use autologous normovolemic hemodilution (ANH), although this method is most helpful in cardiac surgery, because patients benefit from the fresh whole blood with functional clotting factors and PLTs after separation from cardiopulmonary bypass .…”
Section: Strategies For Bloodless Medicinementioning
confidence: 99%